2014
DOI: 10.1093/annonc/mdu348.6
|View full text |Cite
|
Sign up to set email alerts
|

Induction Gemcitabine in Standard Dose or Prolonged Low-Dose with Cisplatin Followed By Concurrent Radiochemotherapy in Locally Advanced Non-Small Cell Lung Cancer: a Randomized Phase Ii Clinical Trial

Abstract: Background The optimal combination of chemotherapy with radiation therapy for treatment locally advanced non-small cell lung cancer (NSCLC) remains an open issue. This randomized phase II study compared gemcitabine in two different schedules and cisplatin - as induction chemotherapy, followed by radiation therapy concurrent with cisplatin and etoposid. Patients and methods. Eligible patients had microscopically confirmed inoperable non-metastatic non-small cell lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The results of PFS and OS in our series of patients with stage III NSCLC treated with durvalumab after ChT-RT confirmed improved survival compared to our historical data of treatment before durvalumab introduction. [10][11][12] After the median follow-up time of 23 months, 12-and 24-month PFS (71% and 45.8%, respectively) and OS (86.7% and 68.6%, respectively) in our series were comparable with those in the PACIFIC trial (PFS 55.3% and 44.8% and OS 83.1% and 66.3%). [1][2][3][4] In addition, data from other real-world reports have confirmed the advantage of maintenance treatment with durvalumab over ChT-RT only.…”
Section: Discussionsupporting
confidence: 79%
“…The results of PFS and OS in our series of patients with stage III NSCLC treated with durvalumab after ChT-RT confirmed improved survival compared to our historical data of treatment before durvalumab introduction. [10][11][12] After the median follow-up time of 23 months, 12-and 24-month PFS (71% and 45.8%, respectively) and OS (86.7% and 68.6%, respectively) in our series were comparable with those in the PACIFIC trial (PFS 55.3% and 44.8% and OS 83.1% and 66.3%). [1][2][3][4] In addition, data from other real-world reports have confirmed the advantage of maintenance treatment with durvalumab over ChT-RT only.…”
Section: Discussionsupporting
confidence: 79%
“…Multiple small underpowered studies prior to ours have tried to address this question and a recent meta analysis of these studies suggested that low dose gemcitabine with prolonged infusion leads to a similar 1 year OS and has a lower rate of leukopenia and thrombocytopenia [12], [13], [14], [20], [21], [22], [23]. However, the authors had cautioned that the evidence was of low quality and a high quality large trial was required to answer this question and to test the validity of their results.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1137 articles were identified by the initial search strategy. After examining the titles and full-text, six identified RCTs [ 7 9 , 13 – 15 ] were selected for the meta-analysis ( Fig 1 ). Nine trials were excluded because they were not randomized [ 6 , 10 , 16 – 21 ] or because the data was unavailable[ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another type of infusion is P-LDI, and several clinical trials [ 7 9 ] were established to evaluate the efficacy and safety of GEM at 30 min-SDI compared with P-LDI in patients with advanced NSCLC. In a phase I–II trial, GEM with a 6 h infusion in combination with cisplatin was used to the treat advanced NSCLC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation